Impact assessment of the Australian 2019–20 megafires on roost sites of the vulnerable grey-headed flying-fox (Pteropus poliocephalus) - Matthew Mo; Jessica Meade; Adam Roff; Libby A. Timmiss; Rebecca Gibson; Justin A. Welbergen (Global Ecology and Conservation, 2024)
Bushfires are a natural component of the ecology of many landscapes, but megafires such as those experienced in Australia between July 2019 and April 2020 have substantial direct and indirect impacts on wildlife. Following these megafires, bushfires have begun to be considered a significant emerging threat to the vulnerable grey-headed flying-fox (Pteropus poliocephalus). In this study, we quantified the impact of the 2019–20 megafires on all known roost locations of the species by (1) determining the number of roosts within burnt areas represented by three fire severity mapping products, (2) classifying burnt roosts according to the severity with which they burnt, and (3) examining the distribution of distances to the nearest burnt areas for unburnt roosts. Our findings indicate that the impacts of the 2019–20 megafires on roosting habitat of the grey-headed flying-fox have hitherto been underestimated. Of 874 known grey-headed flying-fox roosts, we found that 134 roosts were situated within burnt areas, equating to 15 % of the species’ roost locations. Depending on the mapping products applied, part or all canopy vegetation was severely burnt in 27–36 % of burnt roosts, while in 11–14 % of burnt roosts, the canopy vegetation was burnt entirely. Of the 740 unburnt roosts, 50 % were located within 6.85 km from burnt areas, suggesting that, at a substantial number of roosts, flying-foxes were also indirectly affected by the fires, through the effects of smoke on roosting and locally foraging individuals, and through destruction of local foraging resources from burning. We discuss the implications of these findings for the conservation management of this vulnerable species.